2022
DOI: 10.1088/1742-6596/2303/1/012057
|View full text |Cite
|
Sign up to set email alerts
|

Research on Two-Way Detection of YOLO V5s+Deep Sort Road Vehicles Based on Attention Mechanism

Abstract: YOLO v5 was born when Joseph Redmon, the father of YOLO, announced his retirement from the field of computer vision, and its structure was further optimized on the basis of YOLO v4. After the sort target tracking algorithm was proposed, the deep sort algorithm added the optimization of apparent features on the basis of the sort algorithm, which enables the model to be more suitable for practical situations and more mature for vehicle detection on traffic roads. Focusing on the new direction of road traffic det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…The network structure is shown in Figure 2. The convolution kernel is set alternately by 3x3 and 1x1, which is more conducive to the extraction of sea target features 9 . The convolution layer extracts the features and then down-sampling by the pooling layer to remove the unimportant parts of the feature map, and finally outputs the final feature in Figure 3.…”
Section: Yolo-v5 Feature Extractionmentioning
confidence: 99%
“…The network structure is shown in Figure 2. The convolution kernel is set alternately by 3x3 and 1x1, which is more conducive to the extraction of sea target features 9 . The convolution layer extracts the features and then down-sampling by the pooling layer to remove the unimportant parts of the feature map, and finally outputs the final feature in Figure 3.…”
Section: Yolo-v5 Feature Extractionmentioning
confidence: 99%
“…To address this issue, an effective measure to ensure the safe and optimise use o f the prayer facility, particularly during peak prayer times is compulsory. Such improvements may include capacity limits, proper ventilation, enhanced sanitation protocols, and public awareness o f the importance of healthy behavior in communal spaces [7]- [9]. By doing so, the adverse consequences of overcrowding can be reduced by public health promotions and maintain the solemnness o f these communal prayer spaces.…”
mentioning
confidence: 99%
“…Lastly, recent studies have suggested using YOLOv5, a state-of-the-art object detection algorithm, in combination with a robust object tracking algorithm like StrongSORT or DeepSORT, in order to improve the effectiveness of object counting [6] [7]. However, these algorithms may not work as well in more complex cases involving two-way tracking, where the direction of an object's motion is difficult to track, such as in cases where objects are moving in opposite directions, (i.e.…”
mentioning
confidence: 99%